Encyclopedia of Cold War espionage, spies, and secret operations - Trahair, Richard C.S (Enigma Books, 2012)
Even now, long after the supposed end of the Cold War, previously unknown operations and new names continue to surface. Out of the 350 A-Z main entries, over 30 of them are new. In support of the entries the book includes useful tools, such as a complete chronology of significant espionage activities; a glossary of key terms and individuals.